2009
DOI: 10.1371/journal.pone.0004832
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Epigenetic Silencing Is Triggered by a Transient Reduction in Gene Expression

Abstract: BackgroundAberrant epigenetic silencing plays a major role in cancer formation by inactivating tumor suppressor genes. While the endpoints of aberrant silencing are known, i.e., promoter region DNA methylation and altered histone modifications, the triggers of silencing are not known. We used the tet-off system to test the hypothesis that a transient reduction in gene expression will sensitize a promoter to undergo epigenetic silencing.Methodology/Principal FindingsThe tet responsive promoter (PTRE) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 43 publications
2
23
0
1
Order By: Relevance
“…Spread of methylation may be influenced by competition between the transcriptional machinery and DNA methyltransferases and active transcription may provide protection from de novo methylation [17]. This hypothesis seems to be supported by recent studies showing that a decrease in transcriptional output predisposes to de novo methylation [18,19]. The gradual spread in DNA methylation during the ageing process coupled with the stochastic manner by which methylation is initiated may play a role in the predisposition to sporadic cancers that are typically associated with ageing.…”
Section: X-inactivationmentioning
confidence: 86%
See 1 more Smart Citation
“…Spread of methylation may be influenced by competition between the transcriptional machinery and DNA methyltransferases and active transcription may provide protection from de novo methylation [17]. This hypothesis seems to be supported by recent studies showing that a decrease in transcriptional output predisposes to de novo methylation [18,19]. The gradual spread in DNA methylation during the ageing process coupled with the stochastic manner by which methylation is initiated may play a role in the predisposition to sporadic cancers that are typically associated with ageing.…”
Section: X-inactivationmentioning
confidence: 86%
“…Reductions in transcriptional output may predispose a promoter to DNA methylation [18]. A genetic alteration that affects transcription factor binding, alters an enhancer region or results in the recruitment of a repressor may either protect or predispose a promoter to methylation.…”
Section: Single Base Changes Giving Rise To Epigenetic Errorsmentioning
confidence: 99%
“…We also used this approach to knockdown the HERG potassium channel to mimic an LQT2-type phenotype in iPS-CM. We found that the inducible TetO promoter is partially silenced during the cardiac differentiation process, and this is reported to be due to methylation at CpG dinucleotides (Oyer et al, 2009). This silencing is independent of integration at the AAVS1 locus, as CAG-driven transgenes integrated at the AAVS1 locus remain active after differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This outlines a new model in which extended domains of DNA methylation and histone marks are coordinately established to achieve specific gene expression [55]. A recent study suggests that transient alterations in gene expression can trigger a pathway for aberrant silencing of mammalian gene promoters in which histone deacetylation is a critical early step, while DNA methylation surprisingly, follows in the silencing pathway [56]. The effects of these mechanisms are often evident or can be derived from the response of cells to treatments with various epigenetic drugs.…”
Section: Dysfunctional Histone Modifications and Stem Cells In Ovarian mentioning
confidence: 99%